Enhanced Performance in Polymer Light Emmiting Diode by Using Ultra-thin Conductive Films as the Buffer Layer - Hoai Nam, Nguyen Phuong (Communications in Physics, 2014)
The ultra-thin nanocomposite films based on the nano-crystal TiO_2 (TiO_2-nc) or multi-walled carbon nano-tube (MWCNTs) were prepared and used as the buffer layers in the fabrication of the organic light-emitting diodes (OLEDs). The injection efficiency of the hole and electron was improved by inserting an ultra-thin buffer layer between the electrodes and emissive layer. The turn-on voltage of the device with the buffer layers was lowered from 4 to 2.5V, and the current density was increased from 0.3 to 0.7 mA/mm^2, in comparison with the device without such a buffer layer. These devices showed a high efficiency and good stability.